QIGOON SYSTEM AND YOGA THERAPY AS A MEANS OF PHYSICAL REHABILITATION OF PATIENTS WITH HYPERTENSION: hypertension, physical therapy, Qigong, Yoga therapy, therapeutic gymnastics, massage, blood pressure monitoring, hypertension area index - Kopochynska , Yuliya; Kovalenko, Natalia (The Ukrainian Scientific Medical Youth Journal, 2020)
The article considers the features of the etiopathogenesis of hypertension and the use of methods and means of physical therapy, which combine diet therapy, exercise therapy, swimming, therapeutic massage, physiotherapy, cardio, etc. However, existing physical therapy programs do not have a holistic approach to restoring the health of people with hypertension, so the article explores alternative approaches to the use of health programs for the rehabilitation of patients with hypertension, in particular, the Qigong system and yogatherapy. The developed program of physical rehabilitation for hypertension allows to reduce the index of the area of ​​hypertension, which increases the effectiveness of rehabilitation treatment, has a positive effect on the psycho-emotional and physical condition of the patient, helps to normalize blood pressure, accelerates recovery and recovery.